Battle of Stalingrad: Reflection of Events and Evaluation in Turkish Press during Period of World War II - M. Öztürk; M. M. Vagabov; A. A. Gazieva (Научный диалог)
This article delves into the representation of the Battle of Stalingrad in the pages of the Turkish press. Drawing upon regional Turkish newspapers from the years of World War II, materials shedding light on the Battle of Stalingrad are introduced into scholarly discourse for the first time. The study reveals that the Turkish government managed to navigate the tense diplomatic atmosphere of the wartime period effectively. However, this led to censorship and restrictions imposed on newspapers tasked with providing accurate information to the population during the early war years. Following the Red Army’s success on the Stalingrad front, cover-age of war-related issues in the Turkish press shifted significantly in favor of the USSR, becoming more objective. The novelty of the research lies in a fresh perspective on the research question posed. New sources from Turkish periodicals are introduced into scholarly circulation. The authors conclude that Turkey’s policy of diplomacy duality had a clear impact on newspaper pages, subjecting them to strict censorship and requiring alignment with state directives.